Meningkatkan Self-Awerneess Siswa SD Negeri Pantai Hurip 02 Tentang Pemahaman Pencegahan Pelecehan & Kekerasan Seksual - Agung Saiful (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
During teaching observations at the school, the author encountered cases of physical and verbal harassment as well as sexual violence. The problem started with sexual jokes or shouts made by students at SDN Pantai Hurip 02. While teaching at the school, the author observed the behavior of the victim who felt uncomfortable if he received verbal sexual harassment. Verbal sexual harassment involves sentences or words directed at the victim to humiliate and intimidate them. The authors provide insights for children to help them understand themselves, respect themselves, and differentiate between safe and unsafe touch as effectively as possible. This is done so that students can understand the material presented. This socialization program was carried out at SDN Pantai Hurip 02 and involved 36 students. Efforts to increase students' self-awareness at SDN Pantai Hurip 02 have had a significant positive impact on students. There has been an increase in their knowledge and awareness regarding the prevention of sexual harassment and violence, as well as an increase in their self-awareness. This can be seen from the results of the pre-test and post-test which show an increase in the percentage of students who have high self-awareness by 77%, in the medium category by 13%, and in the high category by 10%. A very significant difference occurred after providing an understanding of preventing sexual harassment and violence. In the low category it decreases to 20%, in the medium category it decreases to 10%, and in the high category it increases to 70%.